KONTRIBUSI PARENTS DAY DALAM MENGEMBANGKAN KREATIVITAS SISWA DI SDI SURYA BUANA, KOTA MALANG - Amiliya Nur Rosyidah; Fatimah Azzahra; Esa Nur Wahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the background, the contribution of the Parents Day program at SDI Surya Buana to student creativity, and identify the supporting and inhibiting factors. This program is motivated by the need to strengthen parental involvement in children's education and create a more interactive and collaborative learning environment. The method used is qualitative with a case study approach, through interviews with teachers, parents and students, as well as direct observation. The results showed that Parents Day made a significant contribution in enhancing students' creativity through activities that emphasize the exploration of ideas, critical thinking, and collaboration between parents and students. School support, active participation of parents, and careful planning are the main supporting factors, although there are challenges related to parents' busy schedules that sometimes hinder their attendance. Overall, the program succeeded in strengthening students' creativity and strengthening the relationship between parents, students, and teachers in supporting students' holistic development and social skills.